اسلامی اقتصادی نظام اورفکرِ اقبال : Islamic Economic System and Teachings of Iqbal - محمد اعظم (Tashkeel e Jadeed, 2024)
Iqbal is a poet cum philosopher. His teachings guide in every aspect of society. Allama Iqbal has presented a clear concept of economy through his poetry and thoughts. He does not look toward Karl Marx for economic guidance, nor does he consider the modern ideas of the West. In fact, the sources of Iqbal's thought are the Qur'an and Sunnah. Fikr-e-Iqbal teaches Islamic economy. In Iqbal's time, Socialism and Capitalism were much discussed. Iqbal critically reviewed these two systems and liked their positive aspects and strongly criticized their negative aspects. Iqbal has declared that the basic sources of wealth belong to Allah. He opposes contemporary economic principles, including atheism. He solely adheres to the economic principles of Islam.